The Palgrave Handbook of Incarceration in Popular Culture - Harmes, Marcus K.; Harmes, Meredith; Harmes, Barbara (Springer International Publishing, 2020)
Editors’ Introduction -- Preface - Professor Jeffrey Ross, University of Baltimore -- Chapter one: Unlocking Prisons: Toward a Carceral Taxonomy - Associate Professor James Oleson, University of Auckland -- Section One: Prison and prisoner representations -- Chapter two: The 1980s behind Bars: the Punitive System in Prison (1987) and Lock Up (1989) - Fernando Gabriel Pagnoni Berns, Juan Juvé and Mariana Zárate, Universidad de Buenos Aires -- Chapter three: Freeing every Last man of Shawshank: a Reading of Frank Darabont’s The Shawshank Redemption - Debaditya Mukhopadhyay, Manikchak College -- Chapter four: Incarceration as a Dated Badge of Honour: The Sopranos and the Screen Gangster in a Time of Flux - Robert Hensley-King, Ghent University -- Chapter five: ‘So Neglect Becomes Our Ally’: Strategy and Tactics in the Chateau D'If in Kevin Reynolds' The Count of Monte Cristo (2002) - Dr Kwasu D Tembo, University of Edinburgh -- Chapter six: Prisons on Screen in 1970s Britain - Dr Marcus K Harmes, Meredith A Harmes, Dr Barbara Harmes, University of Southern Queensland -- Chapter seven: Porridge Reheated: Rewriting the Prison Sitcom - Eleanor March, University of Surrey -- Chapter eight: In the Name of the Father: (Re)Framing the Guildford Four - Dr Fran Pheasant-Kelly, University of Wolverhampton, UK -- Chapter nine: ‘You’re in trouble mate’: Prison and Screen Practice - Dr Lewis Fitz-Gerald, University of New England -- Chapter ten: How Does the Design of the Prison in Paddington 2 (2017) Convey Character, Story and Visual Concept? - Jane Barnwell, University of Westminster -- Section Two: Prisoner reactions to representation -- Chapter eleven: Reading Bronson from Deep on the Inside: An Exploration of Prisoners Watching Prison Films - Dr Victoria Knight, De Montfort University, UK and Dr Jamie Bennett, University of Oxford, UK -- Chapter twelve: Voices from the Inside: Prison Podcasts - Dr Dawn K. Cecil, University of South Florida, St. Petersburg -- Chapter thirteen: A Place to Stand: the Importance of Inmate Narratives in Media - Nathan Young, Arizona State University -- Chapter fourteen: Mediated Representations of Prisoner Experience and Public Empathy - Dr Katrina Clifford, Deakin University and Professor Rob White, University of Tasmania -- Section Three: Out of the depths: media creations from inside prison -- Chapter fifteen: Prison on Screen in Italy: From ‘Shame Therapy’ Propaganda to Citizenship Programs - Dr Nicoletta Policek, University of Cumbria, UK -- Chapter sixteen: Make Do and Mend: Images and Realities of Prisoners’ Positive Creativity - Charlotte Bilby, Reader in Criminology, Northumbria University -- Chapter seventeen: ‘O Prison Darkness … Lions in the Cage’; The ‘Peculiar’ Prison Narratives of Guantánamo Bay - Dr Josephine Metcalf, University of Hull -- Chapter eighteen: Ghost Ships in the Sea: Guantánamo Bay Detainee Art and a Torturous Exhibition - Emilee Grunow, University of Minnesota--Twin Cities -- Section Four: Learning from prison: ethics, education, and audiences -- Chapter nineteen: The Lord of the Flies in Palo Alto - Professor James Oleson, Auckland University -- Chapter twenty: Story as ‘Freedom,’ Story as ‘Prison’: Narrative Invention and Human Rights Interventions in Camp 14: Total Control Zone - Professor David Scott Diffrient, Colorado State University -- Chapter twenty-one: An Evaluation of the Effect of Prison Break on Youth Perception of Prison - Dr Okechukwu Chukwuma, Islamic University in Uganda, Kampala Campus and Julius Omokhunu, Edo State, Nigeria -- Section Five: Sensational prisons: incarceration and punishment as reality TV -- Chapter twenty-two: Tacumbú in the News: Non-Sensational Reporting of a Perpetually Unfolding Real-Life Prison Drama - Timothy Revett, New Orleans Baptist Theological Seminary -- Chapter twenty-three: Bad Teens, Smug Hacks & Good TV: The success and legacy of Scared Straight! - Catherine Harrington, Northwestern University, Evanston, IL -- Chapter twenty-four: The Same, but Different: Discourses of Familiarity and Fear in 60 Days In - Dr Faye Davies, Birmingham City University, UK -- Chapter twenty-five: Reality TV: Instilling Fear to Avoid Prison - Dr Erin DiCesare, Johnson C. Smith University -- Chapter twenty-six: The Queen without a Kingdom: Vulnerability, Martyrization, Monolingualism and Injury Towards a Quechua Speaking Woman Imprisoned in Argentina - Dr Sergio Rodríguez-Blanco, Universidad Iberoamericana, Mexico City -- Chapter twenty-seven: Women Behind Bars: Dissecting Social Constructs Mediated by News and Reality TV - Jennifer Thomas, Howard University -- Chapter twenty-eight: Monstrous Celebrity and Train-Wreck Femininity: The Tabloid-isation of Prisons and Prisoners - Dr Susan Hopkins, University of Southern Queensland -- Section Six: Genre and prisons: Black Mirror and beyond -- Chapter twenty-nine: Speculative Punishment, Incarceration, and Control in Black Mirror - Dr David Pierson, University of Southern Maine -- Chapter thirty: Carceral Imaginaries in Science Fiction: Toward a Palimpsestic Understanding of Penality - Kaitlyn Quinn, Department of Sociology, University of Toronto, Erika Canossini, Department of Sociology, University of Toronto Vanessa Evans, Department of English, York University -- Chapter thirty-one: ‘It's more like an eternal waking nightmare from which there is no escape’: Media and Technologies as (Digital) Prison in Black Mirror - Julie Escurignan, University of Roehampton and Dr François Allard-Huver, University of Lorraine -- Chapter thirty-two: Dark Fantasies: The Prisoner and the Future of Imprisonment - Dr Marcus Harmes, Meredith Harmes, Dr Barbara Harmes, University of Southern Queensland -- Chapter thirty-three: Minority Report, Abjection and Surveillance: Futuristic Control in the Scientific Imaginary - Dr Fran Pheasant-Kelly, University of Wolverhampton, UK -- Chapter thirty-four: Moral Ambivalence and the Executioner’s Hood – Averting the Retributive Gaze in Dystopian Fiction - Dr Francine Rochford, La Trobe University, Australia -- Section Seven: Creative and commercial transformations: dark tourism in dark places -- Chapter thirty-five: Dark Tours: Prison Museums and Hotels - Associate Professor James Oleson, Auckland University -- Chapter thirty-six: ‘Pack of thieves?’: The visual representation of prisoners in dark tourist sites - Dr Jenny Wise and Dr Lesley McLean, University of New England, Australia -- Chapter thirty-seven: The Legend of Madman’s Hill: Incarceration, Madness and Dark Tourism on the Goldfields - Dr David Waldron, Federation University Australia -- Chapter thirty-eight: Three Related Danish Narratives: the Film ‘R’, the Penal Museum at Horsens and the Replacement Prison of East Jutland - Dr Jack Dyce -- Chapter thirty-nine: ‘Ulucanlar from Prison to Museum: Struggle on Memory and the Future in Turkey’ - Dr Mine Gencel Bek, University of Siegen -- Section Eight: Orange is the New Black: race and gender in a television phenomenon -- Chapter forty: Introduction to Imprisonment by the ‘Nice White Lady’: Piper Chapman as the Ideal Racialised and Classed Neoliberal Subject - Kate Meakin, University of Sussex -- Chapter forty-one: Can Prison be a Feminist Space?: Interrogating Television Representations of Women’s Prisons - Jessica Ford, University of New South Wales, Australia -- Chapter forty-two: Advocating Prisoners’ Human Rights: A Textual Analysis of Orange is the New Black - Dr Alina Thiemann, Institute of Sociology, the Romanian Academy -- Chapter forty-three: Is Yellow the New Orange? Vis a Vis: The Transnational Phenomenon of Female Prison Dramas and the Rise of Spanish Television - Julia Echeverría, University of Zaragoza, Spain -- Section Nine: Varieties of incarceration: from Wentworth to Bitch Planet -- Chapter forty-four: Wentworth and the Politics and Aesthetics of Representing Female Embodiment in Prison - Cornelia Wächter, Ruhr University Bochum, Germany -- Chapter forty-five: From the Stony Ground Up: the Unique Affordances of the Gaol as ‘Hub’ for Transgressive Female Representations in Women-in-Prison Dramas - Stayci Taylor (RMIT University, Melbourne), Craig Batty (University of Technology, Sydney), Tessa Dwyer (Monash University, Melbourne), Radha O’Meara (University of Melbourne) -- Chapter forty-six: ‘Are You Woman Enough to Survive?’: Bitch Planet’s Collaborative Critique of the Neo-Liberal Prison-Industrial Complex - Dr Martin Zeller-Jacques, Queen Margaret University -- Chapter forty-seven: The Pleasure Politics of Prison Erotica - Dr Nicoletta Policek, University of Cumbria, UK -- Chapter forty-eight: Let’s Have Redemption! Women, Religion and Sexploitation on Screen - Dr Marcus Harmes, Meredith Harmes, Dr Barbara Harmes, University of Southern Queensland -- Section Ten: Exploitation and racialization in prison: film, memoirs and music -- Chapter forty-nine: Screening Fear and Anxiety: African American Incarceration and the Dawning of the Prison-Industrial Complex -...